Philo of Alexandria: on the change of names - Cover, Michael (Philo of Alexandria commentary series, 2024)
"In the treatise On the Change of Names (part of his magnum opus, the Allegorical Commentary), Philo of Alexandria brings his figurative exegesis of the Abraham cycle to its fruition. Taking a cue from Platonist interpreters of Homer's Odyssey, Philo reads Moses's story of Abraham as an account of the soul's progress and perfection. Responding to contemporary critics, who mocked Genesis 17 as uninspired, Philo finds instead a hidden philosophical reflection on the ineffability of the transcendent God, the transformation of souls which recognize their mortal nothingness, the possibility of human faith enabled by peerless faithfulness of God, and the fruit of moral perfection: joy divine, prefigured in the birth of Isaac"--